Correlational Study of Channels of Digital Advertising and Consumers’ Behaviour: A Study of Delta State - Hannah Emuobosa Ivwighren; Oghor Jocye Ogwezi (LOGIKA : Jurnal Penelitian Universitas Kuningan, 2023)
The study seeks to find out the correlation between channels of digital advertising and consumers’ behaviour by looking into the processes of consumer behaviour through the usage of smart gadgets. Digital advertising harnesses the capabilities of digital technology, data analysis, and online channels to create targeted, measurable, and impactful advertising campaigns in the ever-evolving digital landscape. Hinged on the technological determinism theory, the study employed the survey design using 400 copies of structured questionnaire to get data from respondents. To test the hypothesis, 392 copies of properly filled and retrieved questionnaire were analysed using Stata 15.0 software application. The study affirms the spread of social channels, as well as high-quality, low-cost technology, is fuelling the growth of digital advertising. The study establishes that digital advertising may influence brand impression and awareness, as well as generate favourable attitudes toward the offered items. Research, marketers, and advertisers may get useful insights on how to use content aspects to persuade customers to have a good attitude towards advertised products and brands.